Efeitos do exercício físico no controle da glicemia e hemoglobina glicada em pacientes com diabetes durante a pandemia do COVID-19: uma revisão sistemática - Souza, Erivaldo de (2024)
Introduction: The pandemic initiated by COVID-19 caused millions of deaths and negative repercussions throughout the global public health system. People who are infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) face aggravating health circumstances in various organs and systems, in addition, patients with present cardiometabolic conditions may face the worst consequences, people with diabetes mellitus (DM), type 1 and/or type 2 (DM1 and DM2). Objective: Evaluate the effects of physical exercise, as well as physical activity levels in individuals with diabetes on the maintenance of plasma glucose and glycated hemoglobin during the COVID-19 pandemic. Methods: For the systematic review, we searched the databases Web of Science, SciELO, LILACS, Sportdiscus, Bireme/BVS, Google Scholar, SCOPUS, Embase and PubMed. The strategies PICO (to build the research problem and select the articles) and GRADE (to assess the methodological quality of the studies) were used. Results: We identified 2,218 articles and after initial exclusion, by type of study and duplications, 1,521 were selected for analysis of titles and abstracts, of these 16 were eligible for full reading and at the end 7 studies advanced to inclusion in the systematic review. The sample number of participants in the surveys was 1,287 individuals, with a mean age of 37 years with DM1 or DM2. Conclusion: Regular exercise and high levels of physical activity contribute to the maintenance of plasma glucose and glycated hemoglobin (HbA1c) levels in patients with diabetes. In addition, maintaining adequate levels of physical activity (150 a 300min/week) can contribute to reducing the stress caused by the pandemic and maintaining body weight and BMI, and may contribute to reducing the aggravation of COVID-19, when it becomes contaminated.